The Effect of Science-Based Courses on Student Teachers' Biophilia Levels - Esra Ozay Kose; Seyda Gul; Abdurrahman Sefali (Universitas Pendidikan Indonesia, 2023)
This study examines the effect of science-based courses on student teachers' biophilia levels. Based on the quantitative research approach, this study was conducted using a quasi-experimental method. The sample of the study consists of 146 student teachers studying at the education faculty of a state university in the fall semester of the 2022-2023 academic year. The sample group was conducted with student teachers who chose four different science-based courses and voluntarily participated in the study. The Biophilia Scale with 25 items was used as a data collection tool. The findings showed that the biophilia levels of the participants in all four courses showed significant differences in favor of the post-tests. The findings also showed that the